Percentage of primiparous water buffalo cows becoming pregnant in the first 90 days postpartum - Héctor Nava-Trujillo; José Colmenares-Duque; Frank Díaz-Huerta; Adriana Morgado-Osorio; Armando Quintero-Moreno (Revista Científica)
Reproductive performance is a critical factor affecting the profitability of buffalo systems, and parity is a factor affecting reproductive performance. This study aimed to evaluate the effect of parity on the percentage of pregnant buffaloes for day 90 postpartum and determine if the postpartum treatment with GnRH increases the reproductive efficiency of primiparous water buffalo cows. In the first experiment, water buffalo cows from one commercial farm located in Coloncito, Tachira, Venezuela, were grouped into primiparous (n=77) or multiparous (n=341), and the percentage of pregnant buffaloes at day 90 postpartum was compared with Chi-square. In a second experiment, the effect of the treatment with GnRH intramuscular (21 μg of Buserelin acetate, Gestar®, OVER, Argentina) on the rate of pregnant primiparous buffaloes for day 90 postpartum was evaluated. For this, 47 primiparous buffaloes from a commercial farm (La Fria, Tachira, Venezuela) calving between October- December, with a BCS of at least 3 (scale of 1 to 5) and without follicular or luteal structures at day 30 postpartum, were divided into three groups: Control (n=11), no treatment; G30 (n=18), treated with 21μg of GnRH at day 30 postpartum; and G45 (n=18), treated with 21 μg of GnRH at day 45 postpartum. The association between the treatment and the proportion of water buffaloes pregnant at day 90 postpartum was determined with the Chi-square test. In both experiments, animals grazed in pastures consisting of creeping river grass (Echinochloa polystachya), tanner (Bachiaria arrecta), and humidicola (Brachiaria humidicola) in one-day paddock rotations. The bull was present continuously with the herd of buffaloes, and the pregnancy diagnosis was carried out by rectal palpation at day 90 postpartum. In experiment 1, the percentage of buffaloes becoming pregnant in the first 90 days postpartum was lower in primiparous (25.97% vs. 43.98%, Chi-square = 6.573, p<0.05). The odds of pregnancy for day 90 in primiparous buffaloes was only 0.4468 (95% CI:0.2571-0.7763) and was statistically significant (p=0.0.0043). In experiment 2, the overall rate of water buffaloes becoming pregnant during the first 90 days postpartum was 59.57% (28/47). In the control group, it was 45.45%, while in the groups treated with GnRH, it was 77.77% for G30 and 50% for G45. The numerical difference in the percentage of pregnant buffaloes between treatment at day 30 versus treatment at day 45 or the control group did not reach statistical significance (p>0.05). Similarly, no significant differences were observed between the control group and the buffaloes treated at day 45 (Chi-square = 0.055, p=0.8152). In a separate experience, on a farm located in Tres Islas, Tachira, Venezuela, 31/34 of primiparous buffaloes treated with 21 μg of GnRH at day 30 postpartum became pregnant (a control group was not included, and therefore no statistical analysis was made). In conclusion, given the lower percentage of primiparous buffaloes becoming pregnant during the first 90 days postpartum, this category must be considered a group with a high risk of reproductive failure, and differential management must be implemented to avoid this situation. Using 21 μg of GnRH at day 30 postpartum resulted only in a numerical increase in pregnancy rate at day 90 postpartum in primiparous buffaloes. Therefore, this treatment could be an economical alternative to improve the reproductive efficiency of primiparous buffaloes calving in the short photoperiod season, managed with natural service, and having a good body condition score. Still, the results of this treatment must be validated with a larger population.